A twentieth century major soluble ion record of dust and anthropogenic pollutants from Inilchek Glacier, Tien Shan. Issue 3 (2nd February 2017) - Grigholm, B.; Mayewski, P. A.; Aizen, V.; Kreutz, K.; Aizen, E.; Kang, S.; Maasch, K. A.; Sneed, S. B.
Abstract: Using a high‐resolution ( 18 samples/year) major soluble ion record (Na +, K +, Mg 2+, Ca 2+, Cl −, NO3 −, and SO4 2− ) covering the period 1908–1995 A.D. from the Inilchek Glacier, Tien Shan, Kyrgyzstan, we provide a detailed climate and environmental proxy record for the region. Chemical concentrations, empirical orthogonal function analyses, and noncrustal excess calculations are used to identify natural and potential anthropogenic depositional trends. Dominant dust proxy species (i.e., Ca 2+ ) reveal highest concentrations during the 1950s–1970s, with declining decadal trends through the end of the record. These trends likely reflect decreases in central Asian dust storm activity post‐1950, which has been associated with coupled atmospheric circulation variability and anthropogenic activities. Comparison between Ca 2+ and ERA‐Interim (1979–1995) climate reanalysis data indicates a strong relationship to spring (March–May) geopotential height patterns in northwest China and southern Siberia associated with the Siberian High. Noncrustal contribution (excess) estimates of NO3 −, K +, SO4 2−, and Cl − concentrations suggest discernable anthropogenic inputs began between the 1950s and 1970s, increased into the middle/late 1980s, and declined in the 1990s. Excess trends coincide with Former Soviet Union consumption, production, and emission of fossil fuels and fertilizers, reflecting the rapid growth of agriculture and industry, as well as economic declines in the middle to late 1980s/early 1990s. Excess‐Cl − trends reflect timings that coincide with the construction of the Pavlodar Chemical Plant and the military production of Cl2 in Kazakhstan. NOAA Hybrid Single‐Particle Lagrangian Integrated Trajectory back trajectory frequency analysis suggests eastern Uzbekistan (e.g., Fergana Valley), Kyrgyzstan, and southern Kazakhstan as the primary pollutant sources to the study region. Key Points: First high‐resolution multidecadal (1908–1995) major soluble ion record from Inilchek glacier, Tien Shan, Kyrgyzstan Highest Ca 2+ concentrations occur between 1950s and 1970s, with declining trends to the 1990s, reflecting decreases in dust storm activity Noncrustal contribution estimates of NO3 −, K +, SO4 2−, and Cl − suggest that discernable anthropogenic inputs began between the 1950s and 1970s